1999
DOI: 10.1007/s004240050864
|View full text |Cite
|
Sign up to set email alerts
|

Use of electrochemical impedance measurements to monitor β-adrenergic stimulation of bovine aortic endothelial cells

Abstract: Due to the high permeability of endothelial cell layers derived from macrovascular vessels, precise determination of their barrier function towards ion movement requires refined experimental techniques. We thus cultured bovine aortic endothelial cells (BAEC) directly on thin gold-film electrodes and measured the electrochemical impedance to study their passive electrical properties in general and during beta-adrenergic stimulation. Impedance spectra (10-2.10(6) Hz) of confluent cell monolayers revealed that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
117
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(122 citation statements)
references
References 31 publications
5
117
0
Order By: Relevance
“…macrovascular endothelial cells). ECIS analysis for these cell monolayers provides R b values of 3 cm 2 and below (Giaever and Keese, 1991;Wegener et al, 1999) with no cells missing in the cell sheet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…macrovascular endothelial cells). ECIS analysis for these cell monolayers provides R b values of 3 cm 2 and below (Giaever and Keese, 1991;Wegener et al, 1999) with no cells missing in the cell sheet.…”
Section: Resultsmentioning
confidence: 99%
“…However, instead of using ultrastructural imaging techniques like EM that are confined to a field of view of one or a few cells at the most, we applied the electrochemical ECIS device that is capable of recording average alterations in cell shape integrated over a cell monolayer of hundreds of cells. ECIS has proven to be extraordinary sensitive to changes in cell-cell and cell-substrate contacts (Wegener et al, 1999;Tiruppathi et al, 1992;Lo et al, 1994). Since the shape of individual cells within a confluent monolayer is determined by their various contacts to their nearest neighbors as well as by their molecular interactions with the growth substrate, ECIS should be well suited to monitor the onset and the dynamics of apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] In addition to these efforts, some researchers have attempted to monitor cellular ligand-receptor interactions using bioimpedance. [26][27][28] This ligand interaction work has focused on the use of a single frequency and has shown that activation of a GPCR can be observed with this technique. 27 However, the results were of limited scope, with no consideration of how receptor specificity, if any, could be manifest in the measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Impedance changes have been used to monitor cell attachment and spreading (3), cell locomotion and micromotion (4), and changes in cell morphology in response to physical and biochemical changes (5,6). Furthermore, these measurements can be coupled with assays as a means to measure the toxicity of compounds (7), signal transduction (8), and the invasive activities of transformed cells in culture (9).…”
mentioning
confidence: 99%